Community context and therapeutic recreation programming in rural long-term care: a socio-ecological examination. Issue 1 (2nd January 2022) - Nelson, Grace M.; Rich, Kyle A.
ABSTRACT: The importance of maintaining wellness for seniors is widely acknowledged, and can be achieved through recreation and leisure programming. Nevertheless, little research has explored the intersection between the rural context and the processes of Therapeutic Recreation (TR) practice and programming within long term care (LTC) settings. Using a qualitative single case study methodology, our research sought to examine this intersection. Semi-structured interviews and document analysis were conducted. The data were analyzed using thematic analysis and the socio-ecological model. The results are presented as two themes. First, we discuss the influence of health care policy and practice on TR programming. Second, we discuss context specific challenges and opportunities of carrying out programming. Implications of a context-focused approach to programming and care are discussed with regards to practice and future research.